Cell surface phenotype of lipopolysaccharides-stimulated peripheral blood mononuclear cells-derived microparticles - Noor, Nur Azira Mohd (Universiti Sains Malaysia, 2016)
Monocytic microparticles (mMP) can be defined as a heterogeneous population of small vesicles with approximate size 0.1 to 1 gm derived from peripheral blood monocytes. Notable elevated levels of circulating microparticles (MP) have been observed in various clinical states, and are significantly associated with disease severity. Previous studies suggest that MP express phosphatidylserine (PS) which contribute in inflammation process. Their release is enhanced by cell injury, cell activation, or apoptosis and can be triggered by lipopolysaccharides (LPS) stimulation. MP display phenotypic and cytosolic compositions that resemble their parental cells. However, study on mMP is limited. To date, the characterization of cell surface mMP is unclear. In this study, we intended to characterize mMP by measuring cell surface expression of mMP including CD 14, CD 16 and PS as well as comparing the level of mMP secretion between stimulated and unstimulated peripheral blood mononuclear cells (PBMC). PBMC were cultured in the presence or absence of LPS for 18 and 24 hours. Monocytic MP secretion was assessed in the supernatants using anti-human CD 14, anti-human CD 16 and Annexin-V. Meanwhile, stimulated PBMC was assessed in culture pellet using anti-human CD14, anti-human CD16, and anti-human CD1 lb. All analyses were performed using flow cytometry. Our experimental data showed that CD 14 and Annexin-V marker were clearly detected on mMP. In contrast, CD 16 marker was undetectable. We observed that mMP production was proportional to stimulation period. LPS-slimulated PBMC secreted higher level of mMP compared to unstimulated PBMC when cultured for 18 and 24 hours. Cell viability of stimulated PBMC remains unchanged. In addition, changes in mean fluorescense intensity 'AM1T of all markers in unstimulated PBMC was higher than stimulated PBMC. These finding suggest that Annexin-V in combination with CD 14 are the potential cell surface markers for mMP detection, while we confirmed that LPS down-regulate the expression of CD 14, CD 16 and CD 1 1 b on stimulated PBMC.